2021
DOI: 10.3390/polym13152503
|View full text |Cite
|
Sign up to set email alerts
|

Kinetical Study, Thermo-Mechanical Characteristics and Recyclability of Epoxidized Camelina Oil Cured with Antagonist Structure (Aliphatic/Aromatic) or Functionality (Acid/Amine) Hardeners

Abstract: In an attempt to prepare sustainable epoxy thermosets, this study introduces for the first time the idea to use antagonist structures (aromatic/aliphatic) or functionalities (acid/amine) as hardeners to produce reprocessable resins based on epoxidized camelina oil (ECMO). Two kinds of mixtures were tested: one combines aromatic/aliphatic dicarboxylic acids: 2,2′-dithiodibenzoic acid (DTBA) and 3,3′-dithiodipropionic acid (DTDA); another is the combination of two aromatic structures with acid/amine functionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The authors observed interesting properties for the camelina derived alkoxy fatty acids which suggested their great potential for low temperature applications as bio-lubricant base stocks and good alternatives for synthetic and mineral oil derived lubricants. 112 In a recent report by Mauro and coworkers (2021), 119 they reported on the synthesis of reprocessable resins derived from epoxidized camelina oil when using antagonistic structures, either aromatic or aliphatic amines or acids, as hardeners. They explored two different combinations: the rst was a combination of aliphatic/aliphatic carboxylic acids (3,3 0 -dithiodipropionic acid, and 2,2 0 -dithiodibenzoic acid), while the second consisted of only aromatic structures with acid/amine functionality (4-aminophenyl disulde, and 2,2 0 -dithiodibenzoic acid).…”
Section: Coatings and Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed interesting properties for the camelina derived alkoxy fatty acids which suggested their great potential for low temperature applications as bio-lubricant base stocks and good alternatives for synthetic and mineral oil derived lubricants. 112 In a recent report by Mauro and coworkers (2021), 119 they reported on the synthesis of reprocessable resins derived from epoxidized camelina oil when using antagonistic structures, either aromatic or aliphatic amines or acids, as hardeners. They explored two different combinations: the rst was a combination of aliphatic/aliphatic carboxylic acids (3,3 0 -dithiodipropionic acid, and 2,2 0 -dithiodibenzoic acid), while the second consisted of only aromatic structures with acid/amine functionality (4-aminophenyl disulde, and 2,2 0 -dithiodibenzoic acid).…”
Section: Coatings and Adhesivesmentioning
confidence: 99%
“…In a recent report by Mauro and coworkers (2021), 119 they reported on the synthesis of reprocessable resins derived from epoxidized camelina oil when using antagonistic structures, either aromatic or aliphatic amines or acids, as hardeners. They explored two different combinations: the first was a combination of aliphatic/aliphatic carboxylic acids (3,3′-dithiodipropionic acid, and 2,2′-dithiodibenzoic acid), while the second consisted of only aromatic structures with acid/amine functionality (4-aminophenyl disulfide, and 2,2′-dithiodibenzoic acid).…”
Section: Valorization Of Camelina Oil For Industrial Applicationsmentioning
confidence: 99%
“…Mechanical strength, durability, chemical, and thermal resistance, and dimensional stability are all advantages of this material. However, because processed thermoset polymers are crosslinked, recovering the fibers is challenging as they cannot be easily heated, shaped, processed, or re-crosslinked following treatment [ 37 ]. Recycling CFRP trash reduces greenhouse-gas emissions associated with CFRP waste while also providing an inexpensive option to make high-value carbon fibers.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4 d, all of the samples showed an obvious rubber platform after the glass transition. We calculated the crosslinking density of each film by using the cross-linking density calculation formula: v e = E ’/3 RT [ 47 ], where E ’ represents the energy storage modulus under T g + 50 °C, R refers to the gas constant, and T is T g + 50 °C. T g is closely correlated with the cross-linking density and transferred from 30 °C to 46 °C, with T g increasing with the number of prepolymer acetoacetate groups, and lower cystamine-prepared films compared to 1,6-diaminohexane-prepared films, which is consistent with the results obtained by DSC (with the same trend as T g ).…”
Section: Resultsmentioning
confidence: 99%